Making person-centred assessments. (July 2020) - Symonds, Jon; Miles, Caroline; Steel, Mike; Porter, Sue; Williams, Val
Summary: The social care assessment is a 'key interaction' between a person and the local authority with 'critical' importance for determining a person's needs for care and support. In order to achieve this, the guidance requires that assessments must be 'person-centred throughout'. The concept of person-centred practice is now routinely invoked, but there remains little empirical evidence on how it gets put into practice. Findings: This paper draws on interview data from 30 practitioners about their experiences of conducting social care assessments in England. While there was widespread support for the principles of a person-centred approach, tensions emerged for practitioners in three ways: the way in which 'chat' was used to build a relationship or conduct the assessment, whether to conduct the assessment via a conversation or by following the sections on the agency form and the extent to which the assessor should involve and negotiate the contributions of family members. Applications: We argue that each of these dilemmas represents an occasion when a commitment to person-centred practice is negotiated between professionals and service users and sometimes compromised as a result. We consider the possibilities for and constraints on achieving person-centred assessments in a post-Care Act environment and discuss the implications for social work practice and research.